Addition Charcoal to The Diet as A Means to Reduce Costs and Its Effect on Carcass, Intestines Microbial Content, and Economic Indicators in Broilers - Al-hamed, Anwar Mohammed; Kharoufa, Ali Husam (Journal of agricultural, environmental and veterinary sciences, 2022)
This study took place during the period 30/11/2021 – 11/12/2021 in the poultry field of the Livestock Department/College of Agriculture and Forestry/Mosul University, and unsexed one-day-old broiler chicks were breaded collectively, at the second week: the chicks were randomly distributed into four treatments and three replicates/treatment were as follows: - T1: control diet (without added charcoal), T2: the diet +3% charcoal, T3: the diet + 5% charcoal, T4: the diet + 7% charcoal. The results of the data were (p ≤ 0.05) as follows: There was no significant effect on live weight at slaughter, dressing %, carcass parts %, heart %, protein efficiency, productivity yield kg/m2 and the number of Lactobacillus bacteria, and there was a significant increase in the weight of the thigh, carcass yield % and the decrease in fat % to the weight carcass and the increase in net revenue and the percentage of net revenue contribution in the treatment of added charcoal by (7%) and a significant increase in thighs % and in the length of the intestines (cm) and a significant decrease in the number of bacteria (Salmonella and E.coli) in the two additions treatments (5, 7) % charcoal compared with the control treatment, with an increase in the value of the index and the production factor in the last week (marketing age). The aim of the study was to use charcoal as an administrative means to lighten the diet as an attempt to reduce the unit cost of production in addition to an attempt to improve the characteristics of the carcass and the microbial content of the intestine.
Keywords: broiler; charcoal; carcass; intestines microbial; economic indicators